Ethanol Sensing Properties of Nanocrystalline α-MoO3 - Sau, Sucheta; Chakraborty, Sonam; Das, Tanushri; Pal, Mrinal (Frontiers in Materials, 2019)
Ethanol sensors with effective and selective sensitivity are extensively used by traffic police to detect drunken drivers, in wine industries for controlling the fermentation process, food package testing, different medical applications etc. Orthorhombic phase pure α-MoO3 nanoparticles were synthesized via facile sol-gel technique to ethanol sensor. It was observed that the gas sensing response of the sample towards 100 ppm of ethanol vapour is 59% at 350 oC. The response and the recovery time of the gas sensor towards 100 ppm ethanol vapour are found to be 34 s and 70 s, respectively. The main obstacle for a gas sensor to be an excellent breath analyser is to remain insensitive toward the main interfering agent of exhaling human breath i.e. moisture. Prepared sensor is highly selective and shows almost no response toward saturated moisture.